Brazilian Dialysis Survey from 1999 to 2023: trends in demographics, nutritional status, primary disease, and viral serology - Fabiana B. Nerbass; Helbert do N. Lima; Ricardo C. Sesso; Jocemir R. Lugon (Brazilian Journal of Nephrology)
Abstract Introduction: Since 1999, the annual Brazilian Dialysis Survey (BDS) has served as one of the essential primary data sources on the chronic dialysis population in Brazil. We aimed to analyze and report trends in demographic and clinical characteristics and the prevalence of positive viral serology among chronic dialysis patients from 1999 to 2023. Methods: We compared trends in sex distribution, age (elderly >65 years), primary causes of chronic kidney disease (CKD), nutritional status, and the prevalence of positive serology for hepatitis B, hepatitis C, and HIV. The Mann-Kendall test was used to evaluate trends across the entire study period, as well as in the first and second halves. Results: The prevalence of men on dialysis therapy increased slightly from 57% to 59%, while the proportion of elderly individuals rose from 24.9% in 2006 to 36.7% in 2023. Significant changes were observed in nutritional status, with prevalence changes in all categories. Hypertension remained the most prevalent primary cause of CKD; however, its prevalence declined over time, while that of diabetes increased and that of glomerulonephritis decreased. The prevalence of positive serology for hepatitis B and C virus has decreased substantially, whereas that of HIV increased. Conclusion: Overtime, the most striking changes occurred in age, nutritional status, and viral serologies. During the analyzed period, the dialysis population in Brazil has become older and with a higher prevalence of overweight. On the other hand, the prevalence of positive serology for hepatitis B and mainly hepatitis C exhibited a dramatic fall.